Toner for developing electrostatic image, electrostatic image developer, toner cartridge, process cartridge, image forming apparatus, and image forming method
By modifying toner particles with strontium titanate particles of specific size and shape, the issue of fogging in images after startup is addressed, achieving improved dispersibility and charge uniformity for reduced fogging.
Patent Information
- Application Number
- JP2022211914
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2017-07-28
- Filing Date
- 2022-12-28
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2037-12-22
AI Technical Summary
Existing toners experience fogging issues immediately after starting up an image forming apparatus due to the slow charging of toner particles at low humidity and poor dispersibility of strontium titanate particles with cubic or rectangular shapes.
The toner particles are modified with strontium titanate particles having a specific size range (30 nm to 100 nm), circularity (0.82 to 0.94), and surface coverage (3% to 50%) to enhance dispersibility and reduce charge concentration at corners, thereby suppressing fogging.
The modified toner particles effectively suppress fogging in images immediately after starting up the image forming apparatus by ensuring uniform charge distribution and improved dispersibility of strontium titanate particles.
Smart Images

Figure 0007612650000003 
Figure 0007612650000004 
Figure 0007612650000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner for developing an electrostatic image, an electrostatic image developer, a toner cartridge, a process cartridge, an image forming apparatus, and an image forming method. [Background technology]
[0002] Patent Document 1 discloses a developer containing a toner and, as abrasive particles, strontium titanate particles having an average primary particle diameter of 30 nm or more and 300 nm or less, a cubic particle shape and / or a rectangular parallelepiped particle shape, and having perovskite crystals.
[0003] In Patent Document 2, the toner particles have a BET specific surface area of 20 to 50 m 2 / g, and is obtained by mixing strontium titanate containing rectangular parallelepiped particles and hydrophobic silica as external additives.
[0004] Patent Document 3 discloses a toner for developing electrostatic images, in which charge control particles made of strontium titanate that has been surface-treated with silicone oil are attached to and / or embedded on the surfaces of colored particles.
[0005] Patent Document 4 discloses a two-component developer containing 0.1 to 1.0 part by weight of strontium titanate having a weight-average particle size of 30 to 75 nm relative to 100 parts by weight of toner base particles. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2011-203758 A [Patent Document 2] Patent No. 5248511 [Patent Document 3] JP 2011-137980 A [Patent Document 4] JP 2010-44113 A Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has an objective to provide a toner for developing electrostatic images that can suppress fogging that occurs in an image immediately after start-up of an image forming apparatus, compared to when strontium titanate particles present on the surface of toner particles have an average primary particle size of 30 nm or more and 100 nm or less, an average circularity of the primary particles of 0.82 or more and 0.94 or less, but a circularity at 84% of the cumulative total of the primary particles is 0.92 or less, or when the average circularity of the primary particles is 0.82 or more and 0.94 or less, but a circularity at 84% of the cumulative total of the primary particles exceeds 0.92, but the average primary particle size is less than 30 nm. [Means for solving the problem]
[0008] The above problems are solved by the following means. <1> The invention relates to A toner particle and a strontium titanate particle externally added to the toner particle, a toner for developing an electrostatic image, the strontium titanate particles present on the surface of the toner particles having an average primary particle size of 30 nm or more and 100 nm or less, an average circularity of the primary particles of 0.82 or more and 0.94 or less, and a circularity of 84% of the cumulative primary particles exceeding 0.92. .
[0009] <2> The invention relates to the strontium titanate particles present on the surface of the toner particles have a standard deviation of primary particle circularity of 0.04 or more and 2.0 or less; <1> 2. The toner for developing electrostatic images according to claim 1 . <3> The invention relates to the strontium titanate particles present on the surface of the toner particles have a standard deviation of primary particle circularity of 0.04 or more and 1.0 or less; <2> 2. The toner for developing electrostatic images according to claim 1 .
[0010] <4> The invention relates to The moisture content of the strontium titanate particles is 1.5% or more and 10% or less. <1> ~ <3> 10. The toner for developing an electrostatic image according to claim 9, The invention according to <5 is The moisture content of the strontium titanate particles is 2% or more and 5% or less. <4> 2. The toner for developing electrostatic images according to claim 1 .
[0011] <6> The invention relates to The strontium titanate particles have a hydrophobized surface. <1> ~ <5> 10. The toner for developing an electrostatic image according to claim 9, <7> The invention relates to The strontium titanate particles have a surface that has been subjected to a hydrophobic treatment with a silicon-containing organic compound. <6> 2. The toner for developing electrostatic images according to claim 1 . <8> The invention relates to The strontium titanate particles have a surface containing 5% by mass or more and 30% by mass or less of a silicon-containing organic compound relative to the mass of the strontium titanate particles. <7> 2. The toner for developing electrostatic images according to claim 1 . <9> The invention relates to The strontium titanate particles have a surface containing 10% by mass or more and 25% by mass or less of a silicon-containing organic compound relative to the mass of the strontium titanate particles. <8> 2. The toner for developing electrostatic images according to claim 1 . <10> The invention relates to The silicon-containing organic compound is at least one selected from the group consisting of an alkoxysilane compound and a silicone oil. <7> ~ <9> 10. The toner for developing an electrostatic image according to claim 9, <11> The invention relates to The mass ratio (Si / Sr) of silicon (Si) to strontium (Sr) calculated from qualitative and quantitative analysis of fluorescent X-ray analysis of the strontium titanate particles is 0.025 or more and 0.25 or less. <7> ~ <10> 10. The toner for developing an electrostatic image according to claim 9,
[0012] <12> The invention relates to The surface coverage rate of the strontium titanate particles with respect to the toner particles is 3% or more and 50% or less. <1> ~ <11> 10. The toner for developing an electrostatic image according to claim 9, <13> The invention relates to The surface coverage rate of the strontium titanate particles with respect to the toner particles is 3% or more and 30% or less. <12> 2. The toner for developing electrostatic images according to claim 1 .
[0013] <14> The invention relates to The strontium titanate particles are strontium titanate particles doped with a metal element other than titanium and strontium. <1> ~ <13> 10. The toner for developing an electrostatic image according to claim 9, <15> The invention relates to The strontium titanate particles are lanthanum-doped strontium titanate particles. <14> 2. The toner for developing electrostatic images according to claim 1 .
[0014] <16> The invention relates to the strontium titanate particles present on the surface of the toner particles have an average primary particle size of 30 nm or more and 80 nm or less; <1> ~ <15> 10. The toner for developing an electrostatic image according to claim 9, <17> The invention relates to the strontium titanate particles present on the surface of the toner particles have an average primary particle size of 30 nm or more and 60 nm or less; <16> 2. The toner for developing electrostatic images according to claim 1 .
[0015] <18> The invention relates to the toner particles have an average circularity of 0.91 or more and 0.98 or less; <1> ~ <17> 10. The toner for developing an electrostatic image according to claim 9, <19> The invention relates to the toner particles have an average circularity of 0.93 or more and 0.97 or less; <18> 2. The toner for developing electrostatic images according to claim 1 .
[0016] <20> The invention relates to the toner particles are white toner particles; <1> ~ <19> 10. The toner for developing an electrostatic image according to claim 9,
[0017] <21> The invention relates to <1> ~ <20> 2. An electrostatic image developer comprising the toner for developing electrostatic images according to claim 1.
[0018] <22> The invention relates to <1> ~ <20> The toner for developing an electrostatic image according to any one of the above items is contained in the container. A toner cartridge that is detachably attached to an image forming apparatus.
[0019] <23> The invention relates to <21> and a developing unit which develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus.
[0020] <24> The invention relates to An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; <21> a developing means for developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer; a transfer means for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing means for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising:
[0021] <25> The invention relates to a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; <21> The electrostatic image formed on the surface of the image carrier is developed by the electrostatic image developer according to claim 1. a developing step of developing the toner image; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1, Effect of the Invention
[0022] <1> , <16> , <17> , <18> , <19> or <20> According to the invention, there is provided a toner for developing electrostatic images which can suppress fogging occurring in an image immediately after start-up of an image forming apparatus, compared to when strontium titanate particles present on the surface of toner particles have an average primary particle size of 30 nm or more and 100 nm or less, an average circularity of the primary particles of 0.82 or more and 0.94 or less, but a cumulative 84% circularity of the primary particles is 0.92 or less, or when the average circularity of the primary particles is 0.82 or more and 0.94 or less, but a cumulative 84% circularity of the primary particles exceeds 0.92, but the average primary particle size is less than 30 nm.
[0023] <2> or <3> According to the present invention, there is provided a toner for developing electrostatic images which can suppress fogging occurring on an image immediately after starting up an image forming apparatus, as compared with a case in which the standard deviation of the strontium titanate particles is less than 0.04.
[0024] <4> or <5> According to the present invention, there is provided a toner for developing electrostatic images which can suppress fogging that occurs on an image immediately after starting up an image forming apparatus, compared to when the water content of the strontium titanate particles is less than 1.5% by mass or exceeds 10% by mass.
[0025] <6> or <10> According to the present invention, there is provided a toner for developing electrostatic images which can suppress fogging that occurs on an image immediately after starting up an image forming apparatus, compared to when the strontium titanate particles do not have a hydrophobically treated surface.
[0026] <7> , <8> or <9> According to the present invention, there is provided a toner for developing electrostatic images which can suppress fogging that occurs on an image immediately after starting up an image forming apparatus, compared to when the toner has a surface containing less than 5% by mass or more than 30% by mass of a silicon-containing organic compound relative to the mass of the strontium titanate particles.
[0027] <11> According to the present invention, there is provided a toner for developing electrostatic images which can suppress fogging that occurs on an image immediately after start-up of an image forming apparatus, compared to when the mass ratio (Si / Sr) of silicon (Si) to strontium (Sr) calculated from qualitative and quantitative analysis of X-ray fluorescence analysis of the strontium titanate particles is less than 0.025 or exceeds 0.25.
[0028] <12> or <13> According to the present invention, there is provided a toner for developing electrostatic images which can suppress fogging that occurs on an image immediately after starting up an image forming apparatus, compared to when the surface coverage rate of strontium titanate particles relative to the toner particles is less than 3% or exceeds 50%.
[0029] <14> or <15> According to the present invention, there is provided a toner for developing electrostatic images which can suppress fogging that occurs on an image immediately after starting up an image forming apparatus, compared to when the strontium titanate particles are not doped with metal elements other than titanium and strontium.
[0030] <21> , <22> , <23> , <24> or <25> According to the invention, in the strontium titanate particles present on the surface of the toner particles, the average primary particle diameter is 30 nm or more and 100 nm or less, the average circularity of the primary particles is 0.82 or more and 0.94 or less, and the circularity at which 84% of the primary particles accumulate is 0.92 or less, or the average circularity of the primary particles is 0.82 or more and 0.94 or less, and the circularity at which 84% of the primary particles accumulate is 0.92 or less. The present invention provides an electrostatic image developer, a toner cartridge, a process cartridge, an image forming apparatus, or an image forming method that can suppress fogging that occurs on an image immediately after starting up an image forming apparatus, compared to the case where a toner for developing electrostatic images having an average primary particle size of less than 30 nm is used. [Brief description of the drawings]
[0031] [Figure 1A] 1 shows an SEM image of a toner to which SW-360 manufactured by Titan Kogyo Co., Ltd., an example of strontium titanate particles, has been externally added, and a circularity distribution graph of the strontium titanate particles obtained by analyzing the SEM image. [Figure 1B] 13 is an SEM image of a toner to which other strontium titanate particles are externally added, and a graph showing the circularity distribution of the strontium titanate particles obtained by analyzing the SEM image. [Diagram 2] 1 is a schematic diagram illustrating an image forming apparatus according to an embodiment of the present invention; [Diagram 3] FIG. 2 is a schematic diagram illustrating a process cartridge according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0032] Hereinafter, embodiments of the present invention will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the present invention.
[0033] In the present disclosure, when referring to the amount of each component in a composition, in cases where multiple substances corresponding to each component are present in the composition, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified.
[0034] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values before and after "~" as the minimum and maximum values, respectively.
[0035] In this disclosure, the "toner for developing electrostatic images" is also referred to simply as "toner", and the "electrostatic image developer" is also referred to simply as "developer".
[0036] <Toner for developing electrostatic images> The toner according to the present embodiment includes toner particles and strontium titanate particles externally added to the toner particles. That is, the toner according to the present embodiment includes toner particles and strontium titanate particles that are an external additive. In addition, in the toner according to this embodiment, the strontium titanate particles present on the surface of the toner particles have an average primary particle size of 30 nm or more and 100 nm or less, an average circularity of the primary particles of 0.82 or more and 0.94 or less, and a circularity of 84% of the cumulative primary particles exceeds 0.92. Hereinafter, strontium titanate particles present on the surface of toner particles, which have an average primary particle size of 30 nm or more and 100 nm or less, an average circularity of the primary particles of 0.82 or more and 0.94 or less, and a circularity of 84% of the cumulative primary particles exceeding 0.92, are referred to as "specific strontium titanate particles".
[0037] Due to their elemental composition, strontium titanate particles have charging behavior similar to that of titanium oxide. In particular, since strontium has a charging suppressing effect in low humidity environments, strontium titanate particles containing strontium are said to be a material that exhibits less difference in charging behavior due to humidity environments compared to titanium oxide. On the other hand, strontium titanate particles have a perovskite crystal structure and are cubic or rectangular, so that they have poor dispersibility in toner particles when added to toner particles. Also, since strontium titanate particles, which are cubic or rectangular, exist on the surface of toner particles with their corners protruding, it is presumed that charges are concentrated at the exposed corners of the strontium titanate particles during frictional charging, which results in poor charging of the toner. In particular, When printing low-density images under low temperature and humidity conditions (e.g., 10°C and 15% RH), the toner charge build-up tends to be poor, resulting in fog on the image immediately after starting up the image forming apparatus. On the other hand, even if the cubic or rectangular parallelepiped shape is deformed, if the particle diameter is small, the toner particles tend to be embedded in the toner particles, causing fogging.
[0038] As a result of extensive research, the inventors have focused on three shape characteristics of the strontium titanate particles present on the surface of toner particles, namely, the average primary particle size, the average circularity of the primary particles, and the circularity which accounts for 84% of the cumulative total of the primary particles, and have discovered that by controlling these characteristics, the occurrence of the above-mentioned fogging can be suppressed. This is because the above three shape characteristics indicate that the strontium titanate particles are present on the surface of the toner particles in a state of excellent dispersibility and with few corners. From the above, it is believed that in the toner of this embodiment, the strontium titanate particles are present on the surface of the toner particles in a state where the corners are less exposed and they are highly dispersible, which can suppress the occurrence of fogging in images immediately after starting up the image forming apparatus.
[0039] [Specific strontium titanate particles] ·Average primary particle size The average primary particle size of the specific strontium titanate particles is 30 nm or more and 100 nm or less, preferably 30 nm or more and 80 nm or less, and more preferably 30 nm or more and 60 nm or less. By setting the average primary particle size of the specific strontium titanate particles to 30 nm or more, the specific strontium titanate particles are prevented from being embedded in the toner particles, and fogging occurring on the image immediately after the start-up of the image forming apparatus is easily suppressed. Also, by setting the average primary particle size of the specific strontium titanate particles to 100 nm or less, the surface coverage rate of the toner particles is easily increased, and fogging occurring on the image immediately after the start-up of the image forming apparatus is easily suppressed.
[0040] When the average primary particle diameter of the specific strontium titanate particles is within the above range, the strontium titanate particles used as an external additive can be said to have a small diameter. Therefore, when the average primary particle diameter is within the above range, it can be said that the small-diameter strontium titanate particles are present on the surface of the toner particles in a state of excellent dispersibility.
[0041] The primary particle size of the specific strontium titanate particles is the diameter of a circle having the same area as the primary particle image (so-called equivalent circle diameter), and the average primary particle size of the specific strontium titanate particles is the particle size that is 50% cumulative from the smallest diameter side in the number-based distribution of primary particle sizes. The primary particle size of the specific strontium titanate particles is determined by taking an SEM image of the toner to which the strontium titanate particles are externally added, and analyzing the image of at least 300 strontium titanate particles on the toner particles in the SEM image. A specific measurement method will be described in the [Examples] below. It should be noted that this SEM image also confirms that the specific strontium titanate particles are present on the surface of the toner particles in a state of excellent dispersibility.
[0042] The average primary particle size of the specific strontium titanate particles can be controlled by adjusting the average primary particle size of the strontium titanate particles used as an external additive. The average primary particle size of the strontium titanate particles used as an external additive can be controlled, for example, by various conditions when producing the strontium titanate particles by a wet process.
[0043] The specific strontium titanate particles have an average circularity of primary particles of 0.82 or more and 0.94 or less, and the circularity of cumulative 84% of the primary particles exceeds 0.92. Hereinafter, the average circularity of the primary particles of strontium titanate particles will be referred to as "average circularity." The circularity that is 84% cumulative of the primary particles is sometimes referred to as "cumulative 84% circularity." When the average circularity and cumulative 84% circularity are within the above ranges, it can be said that the strontium titanate particles are present on the surface of the toner particles with few corners (the reason for this will be described later). Therefore, it is considered that fogging on images immediately after starting up the image forming apparatus, which occurs due to charge concentration on the corners of the strontium titanate particles, is suppressed.
[0044] In addition, the fact that the average circularity and cumulative 84% circularity of the specific strontium titanate particles are within the above ranges means that the strontium titanate particles used as an external additive also have rounded corners. Therefore, compared with the case where cubic or rectangular strontium titanate particles are used as an external additive, the strontium titanate particles having rounded corners are present on the surface of the toner particles in a state of excellent dispersibility.
[0045] In this embodiment, the circularity of the primary particle of the strontium titanate particle is expressed as 4π × (area of the primary particle image) ÷ (perimeter of the primary particle image). 2 The average circularity of primary particles is the circularity that is a cumulative 50% from the small side in the circularity distribution, and the cumulative 84% circularity of primary particles is the circularity that is a cumulative 84% from the small side in the circularity distribution. The circularity of the specific strontium titanate particles is determined by taking an SEM image of the toner to which the strontium titanate particles are externally added, and analyzing the image of at least 300 strontium titanate particles on the toner particles in the SEM image. A specific measurement method will be described in the [Examples] below.
[0046] The cumulative 84% circularity of the specific strontium titanate particles is an index of a rounded shape. This cumulative 84% circularity will be described below.
[0047] 1A is an SEM image of a toner to which SW-360 manufactured by Titan Kogyo Co., Ltd., an example of strontium titanate particles, is added externally, and a graph of the circularity distribution of the strontium titanate particles obtained by analyzing the SEM image. As the SEM image shows, SW-360 has a main particle shape of a cube, and rectangular parallelepiped particles and spherical particles with a relatively small particle size are mixed. The circularity distribution of SW-360 in this example is concentrated between 0.84 and 0.92, with an average circularity of 0.888 and a cumulative 84% circularity of 0.916. This is thought to reflect the fact that the main particle shape of SW-360 is cube, that the projected image of a cube includes, in order of closest to a circle, a regular hexagon (circularity of approximately 0.907), a flat hexagon, a square (circularity of approximately 0.785), and a rectangle, and that the cubic strontium titanate particles are attached to the toner particles with their corners sharpened, so that the projected image is mainly hexagonal. Considering the above-mentioned actual circularity distribution of SW-360 and the theoretical circularity of a solid projection image, it can be estimated that the cumulative 84% circularity of the primary particles of cubic or rectangular strontium titanate particles is less than 0.92. On the other hand, Figure 1B shows two SEM images (two at different magnifications, with the lower SEM image in Figure 1B being the higher magnification SEM image) of a toner to which another strontium titanate particle is externally added, and a graph of the circularity distribution of the strontium titanate particles obtained by analyzing the SEM images. As shown in the two SEM images (particularly the lower SEM image in Figure 1B), the strontium titanate particles of this example had a rounded shape. The strontium titanate particles of this example had an average circularity of 0.883 and an accumulated 84% circularity of 0.935. From the above, for the specific strontium titanate particles, the cumulative 84% circularity is one of the indicators of a rounded shape, and when it is more than 0.92, it can be said that the shape is rounded.
[0048] The average circularity of the specific strontium titanate particles is from 0.82 to 0.94, more preferably from 0.84 to 0.94, and even more preferably from 0.86 to 0.92, in order to suppress fogging that occurs in an image immediately after starting up an image forming apparatus.
[0049] The average circularity and cumulative 84% circularity of the specific strontium titanate particles can be controlled by adjusting the average circularity and cumulative 84% circularity of the strontium titanate particles used as an external additive. In addition, the average circularity and cumulative 84% circularity of the strontium titanate particles used as an external additive can be controlled, for example, by various conditions when producing the strontium titanate particles by a wet process, the doped metal elements other than titanium and strontium and the doped amounts thereof, etc.
[0050] Standard deviation In this embodiment, the strontium titanate particles present on the surface of the toner particles preferably have a standard deviation of primary particle circularity of 0.04 to 2.0, more preferably 0.04 to 1.0, and further preferably 0.04 to 0.50. Cubic or rectangular strontium titanate particles tend to have a narrow circularity distribution due to their shape, and therefore strontium titanate particles having a standard deviation of primary particle circularity within the above range are an indicator that the strontium titanate particles are not largely composed of cubes or rectangular strontium particles. Therefore, strontium titanate particles having a standard deviation of the circularity of primary particles within the above range exist with few corners on the surface of the toner particles, and fogging of images immediately after starting up the image forming apparatus, which is caused by charge concentration at the corners of the strontium titanate particles, is easily suppressed.
[0051] Here, the standard deviation of the circularity of the primary particles is the standard deviation of the circularity of at least 300 strontium titanate particles on the toner particles, which are subjected to image analysis when determining the above-mentioned circularity. The standard deviation of the circularity of the primary particles can be measured simultaneously with the above-mentioned measurement of the average circularity and cumulative 84% circularity. When calculating the standard deviation of the circularity, strontium titanate particles with primary particles of 20 nm or less are removed from the analysis.
[0052] ·Surface coverage In this embodiment, the strontium titanate particles present on the surface of the toner particles preferably have a surface coverage of 3% or more and 50% or less, and more preferably 3% or more and 30% or less. When the surface coverage of the strontium titanate particles to the toner particles is 5% or more, the effect of the strontium titanate particles is effectively exhibited, and fogging of the image immediately after the start-up of the image forming apparatus is easily suppressed.When the surface coverage of the strontium titanate particles to the toner particles is 50% or less, leakage of the charge of the toner becomes significant under high temperature and high humidity, and the occurrence of fogging due to an insufficient charge amount of the toner can be suppressed.
[0053] The surface coverage rate of strontium titanate particles relative to toner particles is determined by using the SEM images used to measure the average circularity and cumulative 84% circularity described above, and the area analysis tool of the image processing analysis software WinROOF (manufactured by Mitani Shoji Co., Ltd.) for this SEM image.
[0054] [Strontium titanate particles] The strontium titanate particles used as an external additive will be described below. In order to satisfy the above-mentioned average primary particle size of the specific strontium titanate particles, the strontium titanate particles used as an external additive preferably have an average primary particle size of 30 nm or more and 100 nm or less, more preferably 30 nm or more and 80 nm or less, and more preferably 30 nm or more and 60 nm or less. It is more preferable that the length is m or less. When the average primary particle size is 30 nm or more, embedding in the toner particles is suppressed, and when it is 100 nm or less, the amount of surface coverage on the toner particles is easily increased.
[0055] In order to satisfy the above-mentioned average circularity and cumulative 84% circularity of the specific strontium titanate particles, it is preferable to use strontium titanate particles having a rounded shape as the strontium titanate particles used as an external additive. For example, the strontium titanate particles used as an external additive preferably have an average circularity of 0.82 or more and 0.94 or less, more preferably 0.84 or more and 0.94 or less, and even more preferably 0.86 or more and 0.92 or less. When the average circularity is 0.82 or more, the dispersibility in the toner particles is easily improved, and when it is 0.94 or less, the mobility on the surface of the toner particles decreases, and the uniform dispersibility on the surface is easily improved.
[0056] The strontium titanate particles used as an external additive preferably have a half-width of the peak of the (110) plane obtained by X-ray diffraction method of 0.2° or more and 2.0° or less. The (110) plane peak obtained by X-ray diffraction of strontium titanate particles is a peak that appears at a diffraction angle of about 2θ = 32°. This peak corresponds to the (110) plane peak of a perovskite crystal. Strontium titanate particles with a cubic or rectangular shape have high perovskite crystallinity, and the half-width of the peak on the (110) plane is usually less than 0.2°. For example, when SW-350 (strontium titanate particles with a cubic main particle shape) manufactured by Titan Kogyo Co., Ltd. was analyzed, the half-width of the peak on the (110) plane was 0.15°. On the other hand, in strontium titanate particles with a rounded shape, the crystallinity of the perovskite crystal is relatively low, and the half-width of the peak of the (110) plane is broadened. The strontium titanate particles used as an external additive preferably have a rounded shape, and as one indicator of a rounded shape, the half-width of the peak of the (110) plane is preferably 0.2° or more and 2.0° or less, more preferably 0.2° or more and 1.0° or less, and even more preferably 0.2° or more and 0.5° or less.
[0057] X-ray diffraction of strontium titanate particles is performed using an X-ray diffraction device (for example, Rigaku Corporation, product name RINT Ultima-III). The measurement settings are: radiation source CuKα, voltage 4 0 kV, current 40 mA, sample rotation speed: no rotation, divergence slit: 1.00 mm, divergence vertical limiting slit: 10 mm, scattering slit: open, receiving slit: open, scanning mode: FT, counting time: 2.0 seconds, step width: 0.0050°, scanning axis: 10.0000° to 70.0000°. In this disclosure, the half-width of a peak in an X-ray diffraction pattern is the full width at half maximum.
[0058] The strontium titanate particles used as an external additive are preferably doped with a metal element other than titanium and strontium (hereinafter also referred to as a dopant). By including a dopant, the strontium titanate particles have a lower crystallinity of the perovskite structure and a rounded shape.
[0059] The dopant of the strontium titanate particles is not particularly limited as long as it is a metal element other than titanium and strontium. It is preferable that the metal element has an ionic radius that can enter the crystal structure of the strontium titanate particles when ionized. From this point of view, the dopant of the strontium titanate particles is preferably a metal element having an ionic radius of 40 pm or more and 200 pm or less when ionized, and more preferably a metal element having an ionic radius of 60 pm or more and 150 pm or less when ionized.
[0060] Specific examples of the dopant of strontium titanate particles include lanthanoids, silica, aluminum, magnesium, calcium, barium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, gallium, niobium, molybdenum, ruthenium, palladium, indium, antimony, tantalum, tungsten, rhenium, iridium, platinum, bismuth, yttrium, zirconium, niobium, silver, and tin. Preferred lanthanoids are lanthanum and cerium. Among these, lanthanum is preferred from the viewpoint of easy doping and easy shape control of strontium titanate particles.
[0061] As the dopant for the strontium titanate particles, from the viewpoint of preventing the strontium titanate particles from being excessively negatively charged, a metal element having an electronegativity of 2.0 or less is preferable, and a metal element having an electronegativity of 1.3 or less is more preferable. The electronegativity in this embodiment is the Allred-Rochow electronegativity. Suitable metal elements having an electronegativity of 2.0 or less are shown below along with their electronegativity. Metal elements with an electronegativity of 2.0 or less include lanthanum (1.08), magnesium (1.23), aluminum (1.47), silica (1.74), calcium (1.04), vanadium (1.45), chromium (1.56), manganese (1.60), iron (1.64), cobalt (1.70), nickel (1.75), copper (1.75), zinc (1.66), gallium (1.82), yttrium (1.11), zirconium (1.22), niobium (1.23), silver (1.42), indium (1.49), tin (1.72), barium (0.97), tantalum (1.33), rhenium (1.46), and cerium (1.06).
[0062] From the viewpoint of achieving a rounded shape while having a perovskite crystal structure, the amount of dopant in the strontium titanate particles is preferably in the range of 0.1 mol % or more and 20 mol % or less, more preferably in the range of 0.1 mol % or more and 15 mol % or less, and even more preferably in the range of 0.1 mol % or more and 10 mol % or less, relative to strontium.
[0063] The strontium titanate particles used as an external additive preferably have a moisture content of 1.5% by mass or more and 10% by mass or less. When the moisture content is 1.5% by mass or more and 10% by mass or less (more preferably 2% by mass or more and 5% by mass or less), the resistance of the strontium titanate particles is in an appropriate range, and the occurrence of fogging is further suppressed. The moisture content of the strontium titanate particles can be within the above range by producing the strontium titanate particles by a wet process and adjusting the drying treatment conditions (temperature and time). Furthermore, when the surfaces of strontium titanate particles are subjected to a hydrophobic treatment, the above range may be achieved by adjusting the conditions of the drying treatment after the hydrophobic treatment.
[0064] The moisture content of the strontium titanate particles is measured as follows. 20 mg of the measurement sample is left to stand in a chamber at 22°C / 55% relative humidity for 17 hours to condition the humidity, and then heated from 30°C to 250°C at a temperature increase rate of 30°C / min in a nitrogen gas atmosphere using a thermobalance (Shimadzu TGA-50 model) in a room at 22°C / 55% relative humidity, and the heat loss (mass lost due to heating) is measured. Then, the moisture content is calculated based on the measured heat loss using the following formula. Moisture content (mass%) = (heat loss from 30°C to 250°C) ÷ (mass after humidity adjustment before heating) × 100
[0065] From the viewpoint of improving the function of the strontium titanate particles, the strontium titanate particles used as an external additive are preferably strontium titanate particles having a hydrophobized surface, and more preferably strontium titanate particles having a hydrophobized surface with a silicon-containing organic compound. Examples of the silicon-containing organic compound include alkoxysilane compounds, silazane compounds, and silicone oils. Among them, at least one compound selected from the group consisting of alkoxysilane compounds and silicone oils is preferred. The silicon-containing organic compound will be described in detail in the section on the method for producing strontium titanate particles.
[0066] In addition, the strontium titanate particles used as an external additive preferably have a surface that contains a silicon-containing organic compound in an amount of 1% by mass or more and 50% by mass or less (preferably 5% by mass or more and 40% by mass or less, more preferably 5% by mass or more and 30% by mass or less, and even more preferably 10% by mass or more and 25% by mass or less) relative to the mass of the strontium titanate particles. In other words, the amount of hydrophobization treatment using the silicon-containing organic compound is preferably 1 mass% or more and 50 mass% or less, more preferably 5 mass% or more and 40 mass% or less, even more preferably 5 mass% or more and 30 mass% or less, and particularly preferably 10 mass% or more and 25 mass% or less, relative to the mass of the strontium titanate particles. When the amount of hydrophobization is 1% by mass or more, the charge amount of the toner can be secured even under high temperature and high humidity conditions, and the occurrence of fog can be easily suppressed. Also, when the amount of hydrophobization is 50% by mass or less, the saturated charge amount of the toner does not become too large even under low temperature and low humidity conditions, and the occurrence of fog can be easily suppressed. Also, when the amount of hydrophobization is 30% by mass or less, the occurrence of aggregates due to the hydrophobized surface can be easily suppressed.
[0067] From the viewpoint of improving the function of the strontium titanate particles, the hydrophobized surface of the strontium titanate particles preferably has a mass ratio (Si / Sr) of silicon (Si) to strontium (Sr) calculated by qualitative and quantitative analysis using fluorescent X-ray analysis of 0.025 or more and 0.25 or less, and more preferably 0.05 or more and 0.20 or less.
[0068] Here, the fluorescent X-ray analysis of the hydrophobized surface of the strontium titanate particles is carried out by the following method. That is, qualitative and quantitative analysis measurements are performed using a fluorescent X-ray analyzer (Shimadzu Corporation, XRF1500) under conditions of X-ray output of 40 V, 70 mA, measurement area of 10 mmφ, and measurement time of 15 minutes. Here, the elements to be analyzed are oxygen (O), silicon (Si), titanium (Ti), strontium (Sr), and metal elements other than titanium and strontium (Me), and the mass ratio (%) of each element is calculated from the total of each measured element by referring to separately prepared calibration curve data that allows each element to be quantified. The mass ratio (Si / Sr) is calculated based on the silicon (Si) mass ratio value and the strontium (Sr) mass ratio value obtained in this measurement.
[0069] From the viewpoint of improving the chargeability of the toner and further suppressing the occurrence of fog, the strontium titanate particles used as an external additive preferably have a volume resistivity R1 (Ω cm) in common logarithm logR1 of 11 or more and 14 or less, more preferably 11 or more and 13 or less, and even more preferably 12 or more and 13 or less.
[0070] The specific volume resistivity R1 of the strontium titanate particles is measured as follows. A pair of 20 cm electrodes connected to an electrometer (KEYTHLEY, KEITHLEY610C) and a high voltage power supply (FLUKE, FLUKE415B) 2 Strontium titanate particles are placed on the lower electrode of the measurement jig, which is a circular electrode (made of steel), so as to form a flat layer having a thickness in the range of 1 mm to 2 mm. Thereafter, the formed strontium titanate particle layer is conditioned at 22° C. and 55% RH for 24 hours. Next, an upper electrode plate was placed on the humidity-controlled strontium titanate particle layer in an environment of 22°C and 55% RH, and a 4k sintered body was placed on the upper electrode plate to remove voids in the strontium titanate particle layer. A weight of 100 g is placed on the electrode, and the thickness of the strontium titanate particle layer is measured in this state. Next, a voltage of 1000 V is applied to both electrodes to measure the current value, and the specific volume resistivity R1 is calculated from the following formula (1). Equation (1): Volume resistivity R1 (Ω cm) = V × S ÷ (A1-A0) ÷ d In formula (1), V is the applied voltage of 1000 (V), S is the plate area of 20 (cm 2 ), A1 is the measured current value (A), A0 is the initial current value (A) when the applied voltage is 0 V, and d is the thickness (cm) of the strontium titanate particle layer.
[0071] The specific volume resistivity R1 of the strontium titanate particles used as an external additive can be controlled, for example, by the specific volume resistivity R2 of the strontium titanate particles before hydrophobization (R2 varies depending on the water content, the type of dopant, the amount of dopant, etc.), the type of hydrophobization agent, the amount of hydrophobization, the drying temperature and drying time after the hydrophobization, etc. It is preferable that the specific volume resistivity R1 is controlled by at least one of the water content of the strontium titanate particles before hydrophobization and the amount of hydrophobization.
[0072] The volume resistivity R2 of the strontium titanate particles before hydrophobization is preferably 6 to 10 in common logarithm logR2, more preferably 7 to 9. In other words, the inside of the hydrophobized surface of the strontium titanate particles has the above resistance, and the strontium titanate particles have low resistance inside and high resistance on the surface due to the hydrophobization. This improves the chargeability of the toner. In this embodiment, the difference (logR1-logR2) between the common logarithm logR1 of the volume resistivity R1 and the common logarithm logR2 of the volume resistivity R2 is preferably 2 to 7, more preferably 3 to 5, from the viewpoint of improving the chargeability of the toner and ensuring image density.
[0073] The specific volume resistivity R2 of the strontium titanate particles before the hydrophobic treated surface is formed can be controlled by, for example, the water content of the strontium titanate particles, the type of dopant, the amount of dopant, and the like. The specific volume resistivity R2 of the strontium titanate particles before the hydrophobization treatment is measured in the same manner as the specific volume resistivity R1.
[0074] -Method of manufacturing strontium titanate particles- The strontium titanate particles used as the external additive are produced by producing strontium titanate particles and then, if necessary, subjecting the surfaces to a hydrophobic treatment. The method for producing the strontium titanate particles is not particularly limited, but from the viewpoint of controlling the particle size and shape, a wet production method is preferable.
[0075] -Production of strontium titanate particles The wet method for producing strontium titanate particles is, for example, a method in which a mixture of a titanium oxide source and a strontium source is reacted while adding an aqueous alkali solution, and then an acid treatment is performed. In this method, the particle size of the strontium titanate particles is controlled by the mixing ratio of the titanium oxide source and the strontium source, the concentration of the titanium oxide source at the beginning of the reaction, the temperature and the addition rate of the aqueous alkali solution when it is added, etc.
[0076] The titanium oxide source is preferably a mineral acid peptized product of a hydrolyzate of a titanium compound, and the strontium source may be strontium nitrate, strontium chloride, or the like.
[0077] The mixing ratio of the titanium oxide source and the strontium source is SrO / TiO 2 The molar ratio is preferably 0.9 to 1.4, more preferably 1.05 to 1.20. The titanium oxide source concentration at the beginning of the reaction is TiO 2 The concentration is preferably 0.05 mol / L or more and 1.3 mol / L or less, and more preferably 0. A concentration of 5 mol / L or more and 1.0 mol / L or less is more preferable.
[0078] In order to adjust the resistance of the strontium titanate particles, it is preferable to add a dopant source to the mixture of the titanium oxide source and the strontium source. The dopant source may be an oxide of a metal other than titanium and strontium. The metal oxide as the dopant source is added as a solution dissolved in, for example, nitric acid, hydrochloric acid, sulfuric acid, etc. The amount of the dopant source added is preferably an amount in which the dopant metal is 0.1 mol to 10 mol, more preferably an amount in which the dopant metal is 0.5 mol to 10 mol, per 100 mol of strontium.
[0079] The dopant source may be added when the alkaline aqueous solution is added to the mixed solution of the titanium oxide source and the strontium source. In this case, the metal oxide of the dopant source may be added as a solution dissolved in nitric acid, hydrochloric acid, or sulfuric acid.
[0080] The alkaline aqueous solution is preferably a sodium hydroxide aqueous solution. The higher the temperature at which the alkaline aqueous solution is added, the more likely it is that strontium titanate particles with good crystallinity can be obtained. In this embodiment, the temperature is preferably in the range of 60° C. or higher and 100° C. or lower. The slower the addition rate of the alkaline aqueous solution, the larger the particle size of the strontium titanate particles that can be obtained, and the faster the addition rate, the smaller the particle size of the strontium titanate particles that can be obtained. The addition rate of the alkaline aqueous solution is, for example, 0.001 equivalent / h or more and 1.2 equivalent / h or less, and suitably 0.002 equivalent / h or more and 1.1 equivalent / h or less, relative to the charged raw material.
[0081] After the addition of the alkaline aqueous solution, an acid treatment is carried out in order to remove the unreacted strontium source, for example, by adjusting the pH of the reaction solution to 2.5 to 7.0, more preferably 4.5 to 6.0, using hydrochloric acid. After the acid treatment, the reaction liquid is subjected to solid-liquid separation, and the solid content is dried to obtain strontium titanate particles. By adjusting the conditions for drying the solid content, the moisture content of the strontium titanate particles can be controlled. When the surfaces of the strontium titanate particles are subjected to a hydrophobic treatment, the moisture content may be controlled by adjusting the conditions of the drying treatment after the hydrophobic treatment. Here, preferred drying conditions for controlling the moisture content are, for example, a drying temperature of 90°C or higher and 300°C or lower (preferably 100°C or higher and 150°C or lower) and a drying time of 1 hour or higher and 15 hours or lower (preferably 5 hours or higher and 10 hours or lower).
[0082] Hydrophobic treatment The hydrophobization treatment of the surfaces of strontium titanate particles is carried out, for example, by preparing a treatment liquid by mixing a silicon-containing organic compound, which is a hydrophobization agent, with a solvent, mixing the strontium titanate particles with the treatment liquid under stirring, and continuing to stir further. After the surface treatment, a drying treatment is carried out in order to remove the solvent from the treatment solution.
[0083] Examples of the silicon-containing organic compound that is the hydrophobic treatment agent include an alkoxysilane compound, a silazane compound, and silicone oil.
[0084] Examples of alkoxysilane compounds that are hydrophobic treatment agents include tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, ethyltrimethoxysilane, propyltrimethoxysilane, butyltrimethoxysilane, hexyltrimethoxysilane, n-octyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, vinyltriethoxysilane, methyltriethoxysilane, ethyltriethoxysilane, butyltriethoxysilane, hexyltriethoxysilane, and decyltriethoxysilane. , dodecyltriethoxysilane, phenyltrimethoxysilane, o-methylphenyltrimethoxysilane, p-methylphenyltrimethoxysilane, phenyltriethoxysilane, benzyltriethoxysilane; dimethyldimethoxysilane, dimethyldiethoxysilane, methylvinyldimethoxysilane, methylvinyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane; trimethylmethoxysilane, trimethylethoxysilane;
[0085] Examples of the silazane compound that is a hydrophobic treatment agent include dimethyldisilazane, trimethyldisilazane, tetramethyldisilazane, pentamethyldisilazane, and hexamethyldisilazane.
[0086] Examples of silicone oils that are hydrophobic treatment agents include silicone oils such as dimethylpolysiloxane, diphenylpolysiloxane, and phenylmethylpolysiloxane; and reactive silicone oils such as amino-modified polysiloxane, epoxy-modified polysiloxane, carboxyl-modified polysiloxane, carbinol-modified polysiloxane, fluorine-modified polysiloxane, methacryl-modified polysiloxane, mercapto-modified polysiloxane, and phenol-modified polysiloxane.
[0087] Among these, it is preferable to use an alkoxysilane compound as the hydrophobic treatment agent from the viewpoints of charging environmental difference and improving fluidity, and butyltrimethoxysilane is particularly preferable from the viewpoint of improving fluidity.
[0088] As the solvent used in preparing the treatment liquid, when the silicon-containing organic compound is an alkoxysilane compound or a silazane compound, alcohols (e.g., methanol, ethanol, propanol, butanol) are preferred, and when the silicon-containing organic compound is a silicone oil, hydrocarbons (e.g., benzene, toluene, normal hexane, normal heptane) are preferred.
[0089] In the treatment liquid, the concentration of the silicon-containing organic compound is preferably from 1 to 50% by mass, more preferably from 5 to 40% by mass, and even more preferably from 10 to 30% by mass.
[0090] As described above, the amount of the silicon-containing organic compound used in the hydrophobization treatment is preferably 1% by mass or more and 50% by mass or less, more preferably 5% by mass or more and 40% by mass or less, even more preferably 5% by mass or more and 30% by mass or less, and particularly preferably 10% by mass or more and 25% by mass or less, relative to the mass of the strontium titanate particles.
[0091] In this manner, strontium titanate particles having hydrophobized surfaces are obtained.
[0092] ·External addition amount The amount of the strontium titanate particles added externally is preferably 0.1 parts by mass to 5 parts by mass, more preferably 0.5 parts by mass to 3 parts by mass, and even more preferably 0.7 parts by mass to 2 parts by mass, based on 100 parts by mass of the toner particles.
[0093] [Particles other than strontium titanate particles] The toner according to the present embodiment may contain particles other than the above-mentioned strontium titanate as an external additive. The other particles include inorganic particles other than strontium titanate particles. Other inorganic particles include SiO 2 , TiO 2 , Al 2 O 3 , CuO, ZnO, SnO 2 , CEO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O, Na 2 O, ZrO 2 , CaO SiO 2 , K 2 O (TiO 2 )n, Al 2 O 3 2SiO 2 , CaCO 3 , MgCO 3 , BaSO 4 , MgSO 4 etc.
[0094] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobic treatment agent is usually from 1 part by mass to 10 parts by mass with respect to 100 parts by mass of the inorganic particles.
[0095] Other examples of the particles include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, particles of fluorine-based high molecular weight substances), and the like.
[0096] In the additive of this embodiment, when particles other than strontium titanate particles are contained, the content of particles other than strontium titanate particles in the total particles is preferably 15 mass% or less, more preferably 3 mass% or more and 10 mass% or less, and even more preferably 4 mass% or more and 8 mass% or less.
[0097] [Toner particles] The toner particles contain, for example, a binder resin, and, if necessary, a colorant, a release agent, and other additives. In this embodiment, the toner particles are not particularly limited and may be, for example, yellow toner, magenta toner, cyan toner, black toner, white toner particles, transparent toner particles, glitter toner particles, etc.
[0098] -Binding resin- Examples of the binder resin include vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers. Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more.
[0099] The binder resin is preferably a polyester resin, for example a condensation polymer of a polycarboxylic acid and a polyhydric alcohol.
[0100] Examples of polycarboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, Examples of the polycarboxylic acid include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, and sebacic acid), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, examples of the polycarboxylic acid include aromatic dicarboxylic acids. As the polyvalent carboxylic acid, a trivalent or higher carboxylic acid having a crosslinked or branched structure may be used in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acid may be used alone or in combination of two or more kinds.
[0101] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohol may be used alone or in combination of two or more kinds.
[0102] The glass transition temperature (Tg) of the polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), and more specifically, is determined from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."
[0103] The weight average molecular weight (Mw) of the polyester resin is preferably 5000 or more and 1,000,000 or less, and more preferably 7000 or more and 500,000 or less. The number average molecular weight (Mn) of the polyester resin is preferably 2000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight of polyester resin are measured by gel permeation chromatography (GPC). Molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.
[0104] The polyester resin can be obtained by a known production method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a dissolution aid to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the dissolution aid. If a monomer with poor compatibility is present, it is recommended that the monomer with poor compatibility be condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.
[0105] The content of the binder resin is preferably 40% by mass or more and 95% by mass or less with respect to the entire toner particles. The content is preferably from 50% by mass to 90% by mass, and more preferably from 60% by mass to 85% by mass. When the toner particles are white toner particles, the content of the binder resin is preferably 30% by mass or more and 85% by mass or less, and more preferably 40% by mass or more and 60% by mass or less, based on the total amount of the white toner particles.
[0106] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, ultramarine blue, chalco oil blue, methylene blue chlora pigments such as lead oxide, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate, titanium oxide, zinc oxide, calcium carbonate, basic lead carbonate, zinc sulfide-barium sulfate mixture, zinc sulfide, silicon dioxide, and aluminum oxide; and dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based.
[0107] When the toner particles are to be white toner particles, a white pigment may be used as the colorant. As the white pigment, titanium oxide and zinc oxide are preferred, and titanium oxide is more preferred.
[0108] The colorant may be used alone or in combination of two or more kinds.
[0109] The colorant may be surface-treated as necessary, and may be used in combination with a dispersant.
[0110] The content of the colorant is preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles. When the toner particles are white toner particles, the content of the white pigment is preferably from 15% by mass to 70% by mass, and more preferably from 20% by mass to 60% by mass, based on the total amount of the white toner particles.
[0111] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.
[0112] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "melting peak temperature" described in the method for determining melting temperature in JIS K7121-1987 "Method for measuring transition temperature of plastics."
[0113] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner particles.
[0114] -Other additives- Examples of other additives include known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.
[0115] [Characteristics of toner particles] The toner particles may be toner particles of a single layer structure, or may be toner particles of a so-called core-shell structure composed of a core (core particle) and a coating layer (shell layer) that coats the core. The toner particles of the core-shell structure are composed of, for example, a core containing a binder resin and, if necessary, a colorant and a release agent, and a coating layer containing a binder resin.
[0116] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.
[0117] The volume average particle size of the toner particles is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size of each particle in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture of 100 μm in diameter. The number of particles sampled is 50,000. For the measured particle diameters, a cumulative volume-based distribution is drawn from the smallest diameter side, and the particle diameter at which the cumulative 50% is reached is defined as the volume average particle diameter D50v.
[0118] In this embodiment, the average circularity of the toner particles is not particularly limited, but from the viewpoint of improving the cleaning properties of the toner from the image carrier, it is preferably 0.91 or more and 0.98 or less, more preferably 0.94 or more and 0.98 or less, and even more preferably 0.95 or more and 0.97 or less. The small-diameter, rounded strontium titanate particles described above can be dispersed without uneven distribution on the surface of the toner particles. This is the same even when the irregularly shaped toner particles described above are used, and uneven distribution in minute recesses does not occur, and the strontium titanate particles can be dispersed almost uniformly on the surface of the toner particles. That is, even when toner particles having such an irregular shape are used, the toner configuration according to the present embodiment can be obtained, and fogging occurring on an image immediately after starting up the image forming apparatus can be suppressed. Of course, even when spherical toner particles having an average circularity of more than 0.98 are used, the toner configuration according to this embodiment can be obtained, and fogging that occurs in an image immediately after starting up the image forming apparatus can be suppressed.
[0119] In this embodiment, the circularity of a toner particle is the perimeter of a circle having the same area as the projected image of the particle divided by the perimeter of the projected image of the particle, and the average circularity of a toner particle is the cumulative circularity of 50% from the smallest side in the distribution of circularity. The average circularity of a toner particle is determined by analyzing at least 3,000 toner particles using a flow-type particle image analyzer. A specific measurement method will be described in the Examples below.
[0120] For example, when the toner particles are produced by the aggregation and coalescence method, the average circularity of the toner particles can be adjusted by adjusting the stirring speed of the dispersion liquid, the temperature of the dispersion liquid, or the retention time of the dispersion liquid in the fusion and coalescence process. can be controlled.
[0121] [Toner manufacturing method] Next, a method for producing the toner according to the present embodiment will be described. The toner according to the exemplary embodiment is obtained by producing toner particles and then externally adding an external additive to the toner particles.
[0122] The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and any known production method may be used. Among these, it is preferable to obtain the toner particles by the aggregation and coalescence method.
[0123] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, The toner particles are manufactured through a process including a step of preparing a resin particle dispersion in which resin particles to be a binder resin are dispersed (resin particle dispersion preparation step), a step of aggregating the resin particles (or other particles, if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions, if necessary) to form aggregated particles (aggregated particle formation step), and a step of heating the aggregated particle dispersion in which the aggregated particles are dispersed, fusing and coalescing the aggregated particles to form toner particles (fusion and coalescence step).
[0124] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant and a release agent will be described, but the colorant and the release agent are used as necessary. Of course, additives other than the colorant and the release agent may be used.
[0125] -Resin particle dispersion preparation process- Along with a resin particle dispersion in which resin particles serving as a binder resin are dispersed, for example, a colorant particle dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.
[0126] The resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.
[0127] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.
[0128] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.
[0129] In the resin particle dispersion, the resin particles can be dispersed in the dispersion medium by general dispersion methods such as a rotary shear type homogenizer, a ball mill with media, a sand mill, or a dyno mill. Depending on the type of resin particles, the resin particles may be dispersed in the dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method involves dissolving the resin to be dispersed in a hydrophobic organic solvent in which the resin is soluble, adding a base to the organic continuous phase (O phase) to neutralize it, and then introducing an aqueous medium (W phase) to invert the phase from W / O to O / W, and dispersing the resin in the aqueous medium. This is a method of dispersing particles in a medium.
[0130] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (for example, LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are measured in the same manner.
[0131] The content of the resin particles in the resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.
[0132] In the same manner as the resin particle dispersion liquid, for example, a colorant particle dispersion liquid and a release agent particle dispersion liquid are also prepared. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion liquid are the same for the colorant particles dispersed in the colorant particle dispersion liquid and the release agent particles dispersed in the release agent particle dispersion liquid.
[0133] -Agglomerated particle formation process- Next, the resin particle dispersion, the colorant particle dispersion, and the release agent particle dispersion are mixed together, and the resin particles, the colorant particles, and the release agent particles are hetero-aggregated in the mixed dispersion to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.
[0134] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, glass transition temperature of the resin particles -30°C or more and glass transition temperature -10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form aggregated particles. In the aggregated particle formation process, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.
[0135] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the surfactant used is reduced, and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ion of the flocculant may be used together with the flocculant. As this additive, a chelating agent is preferably used.
[0136] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is preferably from 0.01 to 5.0 parts by mass, and more preferably from 0.1 to less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.
[0137] -Fusion / unification process- Next, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the resin particles (for example, a temperature 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to fuse and coalesce the aggregated particles to form toner particles.
[0138] Through the above steps, toner particles are obtained. After obtaining the aggregated particle dispersion in which the aggregated particles are dispersed, the toner particles may be produced through a process of further mixing the aggregated particle dispersion with a resin particle dispersion in which resin particles are dispersed, and aggregating the aggregated particles so that the resin particles are further attached to the surfaces of the aggregated particles to form second aggregated particles, and a process of heating the second aggregated particle dispersion in which the second aggregated particles are dispersed to fuse and coalesce the second aggregated particles to form toner particles having a core-shell structure.
[0139] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dried toner particles. From the viewpoint of chargeability, the washing process is preferably performed by sufficient substitution washing with ion-exchanged water. From the viewpoint of productivity, the solid-liquid separation process is preferably performed by suction filtration, pressure filtration, etc. From the viewpoint of productivity, the drying process is preferably performed by freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.
[0140] The toner according to the present embodiment is produced, for example, by adding an external additive to the obtained toner particles in a dry state and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.
[0141] <Electrostatic image developer> The electrostatic image developer according to the present embodiment contains at least the toner according to the present embodiment. The electrostatic image developer according to the present embodiment may be a one-component developer containing only the toner according to the present embodiment, or may be a two-component developer in which the toner is mixed with a carrier.
[0142] The carrier is not particularly limited, and may be a known carrier. For example, the carrier may be a coated carrier in which the surface of a core material made of magnetic powder is coated with a resin; a magnetic powder dispersion type carrier in which magnetic powder is dispersed and mixed in a matrix resin; a resin impregnated type carrier in which porous magnetic powder is impregnated with a resin; etc. The magnetic powder dispersion type carrier and the resin impregnated type carrier may be a carrier in which the constituent particles of the carrier are used as a core material, and the surface of the carrier is coated with a resin.
[0143] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; magnetic oxides such as ferrite and magnetite; and the like.
[0144] Examples of the resin and matrix resin for coating include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid ester copolymer, straight silicone resin or its modified product containing organosiloxane bonds, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc. The resin and matrix resin for coating may contain additives such as conductive particles. Examples of the conductive particles include particles of metals such as gold, silver, copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, potassium titanate, etc.
[0145] To coat the surface of the core material with a resin, a method of coating with a coating layer forming solution in which the coating resin and various additives (used as necessary) are dissolved in an appropriate solvent can be mentioned. The solvent is not particularly limited, and may be selected taking into consideration the type of resin used, coating suitability, etc. Specific resin coating methods include an immersion method in which the core material is immersed in the coating layer forming solution; a spray method in which the coating layer forming solution is sprayed on the core material surface; a fluidized bed method in which the coating layer forming solution is sprayed on the core material while it is suspended in flowing air; and a kneader coater method in which the carrier core material and the coating layer forming solution are mixed in a kneader coater and then the solvent is removed; and the like.
[0146] The mixture ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.
[0147] <Image forming device, image forming method> An image forming apparatus / image forming method according to this embodiment will be described. The image forming apparatus according to the present embodiment includes an image carrier, a charging means for charging the surface of the image carrier, an electrostatic image forming means for forming an electrostatic image on the surface of the charged image carrier, a developing means for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer means for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing means for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.
[0148] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.
[0149] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is secondarily transferred to the surface of a recording medium; an apparatus equipped with a cleaning means for cleaning the surface of the image holder after the transfer of the toner image and before charging; and an apparatus equipped with a discharging means for irradiating the surface of the image holder with discharging light to discharge it after the transfer of the toner image and before charging it. When the image forming apparatus according to the present embodiment is an intermediate transfer type apparatus, the transfer means has, for example, an intermediate transfer body onto whose surface a toner image is transferred, a primary transfer means which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer means which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.
[0150] In the image forming apparatus according to the present embodiment, for example, a portion including the developing means may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge including the developing means that contains the electrostatic image developer according to the present embodiment is preferably used.
[0151] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.
[0152] FIG. 2 is a schematic diagram showing the configuration of the image forming apparatus according to the present embodiment. The image forming apparatus shown in FIG. 2 is a device for forming an image of yellow (Y), magenta (M), and red (Y) based on color-separated image data. The image forming apparatus includes first to fourth image forming units 10Y, 10M, 10C, and 10K (image forming means) of an electrophotographic type that output images of each color: ink (M), cyan (C), and black (K). These image forming units (hereinafter, simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachably attached to the image forming apparatus.
[0153] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (an example of an intermediate transfer body) 20 is provided to extend through each unit. The intermediate transfer belt 20 is provided wound around a drive roll 22 and a support roll 24 that are in contact with the inner surface of the intermediate transfer belt 20, and runs in a direction from the first unit 10Y to the fourth unit 10K. A force is applied to the support roll 24 by a spring or the like (not shown) in a direction away from the drive roll 22, and tension is applied to the intermediate transfer belt 20 wound around them. An intermediate transfer belt cleaning device 30 is provided on the image bearing surface side of the intermediate transfer belt 20, facing the drive roll 22.
[0154] The developing devices (an example of developing means) 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with yellow, magenta, cyan, and black toners contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.
[0155] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative.
[0156] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging means) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming means) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device (an example of a developing means) 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll (an example of a primary transfer means) 5Y that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of an image carrier cleaning means) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order.
[0157] The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20, and is provided at a position facing the photoconductor 1Y. A bias power supply (not shown) that applies a primary transfer bias is connected to the primary transfer rolls 5Y, 5M, 5C, and 5K of each unit. Each bias power supply changes the value of the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).
[0158] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity of 1×10 at 20° C.-6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam, the resistivity of the portion irradiated with the laser beam changes. Therefore, the exposed surface of the charged photoreceptor 1Y is irradiated with a laser beam 3Y from the exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). As a result, an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0159] The electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charge, and is detected by the laser beam 3Y. As a result, the resistivity of the irradiated portion of the photosensitive layer decreases, causing the electric charge on the surface of the photoconductor 1Y to flow, while the electric charge remains in the portion not irradiated by the laser beam 3Y, forming a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y rotates to a predetermined developing position as the photoconductor 1Y travels. At this developing position, the electrostatic image on the photoconductor 1Y is developed into a toner image by the developing device 4Y and made visible.
[0160] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.
[0161] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y. The toner remaining on the photoreceptor 1Y is removed and collected by the photoreceptor cleaning device 6Y.
[0162] The primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K in the second unit 10M and subsequent units is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of each color are transferred and superimposed.
[0163] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer means) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, and the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.
[0164] The recording paper P onto which the toner image has been transferred is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in a fixing device (one example of a fixing means) 28, where the toner image is fixed onto the recording paper P to form a fixed image. After the color image has been fixed, the recording paper P is conveyed toward a discharge portion, and a series of color image forming operations is completed.
[0165] The recording paper P onto which the toner image is transferred is, for example, plain paper used in electrophotographic copying machines, printers, etc. The recording medium is not limited to the recording paper P, and may also be an OHP sheet or the like. In order to further improve the smoothness of the image surface after fixing, the recording paper P is The surface is also preferably smooth. For example, coated paper in which the surface of ordinary paper is coated with a resin or the like, art paper for printing, etc. are preferably used.
[0166] <Process cartridges, toner cartridges> The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment, is equipped with a developing means that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachably attached to an image forming apparatus.
[0167] The process cartridge according to this embodiment may be configured to include a developing means and, if necessary, at least one selected from other means such as an image carrier, a charging means, an electrostatic image forming means, and a transfer means.
[0168] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.
[0169] FIG. 3 is a schematic diagram showing an example of a process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 3 is configured by, for example, a housing 117 having a mounting rail 116 and an opening 118 for exposure, and integrally combining and holding a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging means) provided around the photoconductor 107, a developing device 111 (an example of a developing means), and a photoconductor cleaning device 113 (an example of a cleaning means), which are assembled into a cartridge. In FIG. 3, 109 indicates an exposure device (an example of an electrostatic image forming means), 112 indicates a transfer device (an example of a transfer means), 115 indicates a fixing device (an example of a fixing means), and 300 indicates a recording paper (an example of a recording medium).
[0170] Next, the toner cartridge according to this embodiment will be described. The toner cartridge according to the present embodiment is a toner cartridge that contains the toner according to the present embodiment and is detachably attached to an image forming apparatus. The toner cartridge contains replenishment toner to be supplied to a developing unit provided in the image forming apparatus.
[0171] 2 is an image forming apparatus having a configuration in which toner cartridges 8Y, 8M, 8C, and 8K are detachably attached, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective colors by toner supply pipes (not shown). When the toner contained in a toner cartridge becomes low, the toner cartridge is replaced. EXAMPLES
[0172] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" are based on mass.
[0173] <Preparation of strontium titanate particles> [Strontium titanate particles (1)] The desulfurized and peptized titanium source, metatitanic acid, was treated with TiO 20.7 moles of strontium chloride was collected and placed in a reaction vessel. Then, an aqueous solution of strontium chloride was added to the reaction vessel, and the SrO / TiO 2 0.77 moles were added so that the molar ratio was 1.1. Next, a solution of lanthanum oxide dissolved in nitric acid was added to the reaction vessel in an amount that gave 5 moles of lanthanum per 100 moles of strontium. 2 The concentration was adjusted to 0.75 mol / L. The mixture was then stirred and heated to 90°C. 153mL of 10N aqueous sodium hydroxide solution was added over 3.8 hours while maintaining the liquid temperature at 90°C and stirring was continued for 1 hour while maintaining the liquid temperature at 90°C. The reaction liquid was then cooled to 40°C, hydrochloric acid was added until the pH reached 5.5, and stirring was continued for 1 hour. The precipitate was then washed by repeating decantation and dispersion in water. Hydrochloric acid was added to the slurry containing the washed precipitate to adjust the pH to 6.5, and solid-liquid separation was performed by filtration. Next, an alcohol solution of i-butyltrimethoxysilane was added to the obtained solid content (strontium titanate particles) in an amount of 20 parts of i-butyltrimethoxysilane per 100 parts of the solid content, and the mixture was stirred for 1 hour. Thereafter, solid-liquid separation was performed by filtration, and the solid content was dried in air at 110° C. for 5 hours to obtain strontium titanate particles (1).
[0174] [Strontium titanate particles (2)~(14), (16)] Metatitanic acid TiO 2 Amount of strontium chloride used [mol], amount of strontium chloride aqueous solution added (amount of SrO) [mol], SrO / TiO 2Strontium titanate particles (2) to (14) were produced in the same manner as in the production of strontium titanate particles (1), except that the molar ratio, the amount of lanthanum added per 100 moles of strontium [moles], the amount of 10 N sodium hydroxide aqueous solution added [mL], the addition time of the 10 N sodium hydroxide aqueous solution [hours], the type of hydrophobizing agent and the treatment amount [parts] per 100 parts of solids, and the drying temperature [°C] and drying time of the strontium titanate particles after the hydrophobizing treatment were appropriately changed as shown in Table 1 below.
[0175] [Strontium titanate particles (15)] Strontium titanate particles (15) were prepared in the same manner as for the preparation of strontium titanate particles (1), except that the alcohol solution of i-butyltrimethoxysilane was changed to silicone oil (KF-96-100CS, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0176] [Table 1]
[0177] <Preparation of toner particles> [Toner particles (1)] - Preparation of resin particle dispersion (1) - Terephthalic acid: 30 parts by mole Fumaric acid: 70 parts by mole Bisphenol A ethylene oxide adduct: 5 mole parts Bisphenol A propylene oxide adduct: 95 parts by mole The above materials were charged into a flask equipped with a stirrer, a nitrogen inlet tube, a temperature sensor, and a distillation column, and the temperature was raised to 220°C over 1 hour, and 1 part of titanium tetraethoxide was added for 100 parts of the above materials. The temperature was raised to 230°C over 30 minutes while distilling off the generated water, and the dehydration condensation reaction was continued at that temperature for 1 hour, after which the reactant was cooled. Thus, a polyester resin with a weight average molecular weight of 18,000 and a glass transition temperature of 60°C was obtained.
[0178] In a vessel equipped with a temperature control means and a nitrogen substitution means, 40 parts of ethyl acetate and 25 parts of 2-butanol were added to prepare a mixed solvent, and then 100 parts of polyester resin were gradually added and dissolved therein, and a 10% by mass aqueous ammonia solution (equivalent to 3 times the amount by molar ratio relative to the acid value of the resin) was added thereto and stirred for 30 minutes. Next, the inside of the vessel was substituted with dry nitrogen, the temperature was kept at 40°C, and 400 parts of ion-exchanged water was added dropwise at a rate of 2 parts / min while stirring the mixed liquid. After the dropping was completed, the temperature was returned to room temperature (20°C to 25°C), and bubbling with dry nitrogen was performed for 48 hours while stirring to obtain a resin particle dispersion liquid in which ethyl acetate and 2-butanol were reduced to 1000 ppm or less. Ion-exchanged water was added to the resin particle dispersion liquid to adjust the solid content to 20% by mass, and a resin particle dispersion liquid (1) was obtained.
[0179] - Preparation of colorant particle dispersion (1) - Regal 330 (Cabot carbon black): 70 parts Anionic surfactant (Daiichi Kogyo Seiyaku, Neogen RK): 5 parts - Ion-exchanged water: 200 parts The above materials were mixed and dispersed for 10 minutes using a homogenizer (IKA, product name Ultra Turrax T50). Ion-exchanged water was added so that the solid content in the dispersion was 20 mass %, and a colorant particle dispersion (1) in which colorant particles with a volume average particle size of 170 nm were dispersed was obtained.
[0180] - Preparation of release agent particle dispersion (1) - Paraffin wax (Nippon Seiro, HNP-9): 100 parts Anionic surfactant (Daiichi Kogyo Seiyaku, Neogen RK): 1 part Ion-exchanged water: 350 parts The above materials were mixed and heated to 100°C, dispersed using a homogenizer (IKA, product name Ultra Turrax T50), and then dispersed using a Manton-Gaulin high-pressure homogenizer (Gaulin), to obtain a release agent particle dispersion (1) (solid content 20% by mass) in which release agent particles having a volume average particle size of 200 nm were dispersed.
[0181] - Preparation of toner particles (1) - Resin particle dispersion (1): 403 parts The above colorant particle dispersion (1): 12 parts The above release agent particle dispersion (1): 50 parts Anionic surfactant (TaycaPower): 2 parts The above materials were placed in a round stainless steel flask, and 0.1N nitric acid was added to adjust the pH to 3.5, and then 30 parts of a nitric acid aqueous solution with a polyaluminum chloride concentration of 10% by mass was added. Then, the mixture was dispersed at a liquid temperature of 30°C using a homogenizer (IKA, product name Ultra Turrax T50), and then heated to 45°C in a heating oil bath and held for 30 minutes. Then, 100 parts of resin particle dispersion (1) was added and held for 1 hour, and 0.1N sodium hydroxide aqueous solution was added to adjust the pH to 8.0, and then heated to 84°C and held for 2.5 hours. Then, the mixture was cooled to 20°C at a rate of 20°C / min, filtered, thoroughly washed with ion-exchanged water, and dried to obtain toner particles (1). The resulting toner particles (1) had a volume average particle size of 5.7 μm and an average circularity of 0.95.
[0182] [Toner particles (2)] Toner particles (2) were prepared in the same manner as in the preparation of toner particles (1), except that 100 parts of resin particle dispersion (1) was added, the mixture was held for 1 hour, a 0.1 N aqueous sodium hydroxide solution was added to adjust the pH to 8.0, and the mixture was heated to 84°C and held for 2.0 hours. The resulting toner particles (2) had a volume average particle size of 5.7 μm and an average circularity of 0.93.
[0183] [Toner particles (3)] -Preparation of colorant particle dispersion (W)- Titanium oxide particles (manufactured by Ishihara Sangyo Kaisha, product name: CR-60-2): 210 parts Anionic surfactant (Neogen RK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.): 10 parts Ion-exchanged water: 480 parts The above components were mixed and stirred for 30 minutes using a homogenizer (IKA Corporation, product name Ultra Turrax T50), and then dispersed for 1 hour using a high-pressure impact disperser Ultimizer (HJP30006: manufactured by Sugino Machine Co., Ltd.) to obtain a white pigment particle dispersion (W) (solid content 30% by mass) in which a white pigment having a volume average particle size of 210 nm was dispersed.
[0184] - Preparation of toner particles (3) - Ion-exchanged water: 600 parts Resin particle dispersion (1): 400 parts The above colorant particle dispersion (W): 325 parts The release agent particle dispersion (1): 78 parts Anionic surfactant (TaycaPower): 8 parts The above materials were placed in a round stainless steel flask, and 0.1N nitric acid was added to adjust the pH to 3.5, and then 13 parts of a nitric acid aqueous solution with a polyaluminum chloride concentration of 10% by mass was added. Next, the mixture was dispersed at a liquid temperature of 30°C using a homogenizer (IKA, product name Ultra Turrax T50), and then heated to 45°C in a heating oil bath and held for 60 minutes. Then, 100 parts of the resin particle dispersion (1) was added and held for 1 hour, and 0.1N sodium hydroxide aqueous solution was added to adjust the pH to 8.5, and then heated to 85°C and held for 5 hours. Next, the mixture was cooled to 20°C at a rate of 20°C / min, filtered, thoroughly washed with ion-exchanged water, and dried to obtain toner particles (3), which are white toner particles. The resulting toner particles (3) had a volume average particle size of 7.5 μm and an average circularity of 0.95.
[0185] <Preparation of carrier> The carrier used was prepared as follows. Ferrite particles (volume average particle size: 36 μm) 100 parts Toluene 14 parts Styrene-methyl methacrylate copolymer 2 parts (Component ratio: 90 / 10, Mw=80000) Carbon black (R330: Cabot Corporation) 0.2 parts First, the above components except for the ferrite particles were stirred with a stirrer for 10 minutes to prepare a dispersed coating liquid. Next, this coating liquid and the ferrite particles were placed in a vacuum degassing kneader and stirred at 60°C for 30 minutes. After that, the mixture was degassed by reducing the pressure while heating, and then dried to obtain a carrier.
[0186] [Preparation of Toner and Developer: Example 1] 0.95 parts of strontium titanate particles (1) were added as an external additive to 100 parts of the toner particles (1), and the mixture was mixed in a Henschel mixer at a stirring peripheral speed of 30 m / sec for 15 minutes to obtain a toner.
[0187] Then, each of the obtained toners and the carrier were placed in a V blender in a ratio of toner:carrier=8:92 (mass ratio), and stirred for 20 minutes to obtain a developer.
[0188] [Preparation of Toner and Developer: Examples 2 to 11, 13, Comparative Examples 1 to 4] A toner and a developer were prepared in the same manner as in Example 1, except that the strontium titanate particles (1) were changed to the strontium titanate particles shown in Table 2 below.
[0189] Preparation of Toner and Developer: Example 12 A toner and a developer were prepared in the same manner as in Example 1, except that the toner particles (1) were changed to the toner particles (2).
[0190] Preparation of Toner and Developer: Example 14 A toner and a developer were prepared in the same manner as in Example 1, except that the toner particles (1) were changed to the toner particles (3).
[0191] <Various analyzes> [Shape characteristics of strontium titanate particles] For the toner, an EDX device (Horiba, EMAX Evolution X-Max 80 mm) 2 ) is attached. Images were taken at a magnification of 40,000 times using a scanning electron microscope (SEM) (Hitachi High-Technologies, S-4800). More than 300 primary particles of strontium titanate were identified within one field of view based on the presence of Ti and Sr by EDX analysis. SEM observations were performed at an accelerating voltage of 15 kV, an emission current of 20 μA, and a WD of 15 mm, and EDX analysis was performed under the same conditions with a detection time of 60 minutes. The identified strontium titanate particles were analyzed using image processing analysis software WinRoof (Mitani Shoji Co., Ltd.) to determine the circle equivalent diameter, area, and perimeter of each primary particle image, and further, the circularity was calculated using the formula: 2 The equivalent circle diameter that is 50% cumulative from the small diameter side in the distribution of equivalent circle diameters was defined as the average primary particle size, the circularity that is 50% cumulative from the small side in the distribution of circularity was defined as the average circularity, and the circularity that is 84% cumulative from the small side in the distribution of circularity was defined as the cumulative 84% circularity. The standard deviation was also determined from the distribution of circularity. The determined values are summarized in Table 2.
[0192] [Surface coverage] The surface coverage of the toner was measured under the above-mentioned measurement conditions. The results are shown in Table 2.
[0193] [X-ray diffraction of strontium titanate particles] The strontium titanate particles before being externally added to the toner particles were used as samples, and crystal structure analysis was performed by X-ray diffraction under the measurement conditions described above. Strontium titanate particles (1) to (10) have a peak at a diffraction angle 2θ of about 32°, which corresponds to the peak of the (110) plane of the perovskite crystal, and the half-width of each peak is in the range of 0.2° or more and 0.5° or less.
[0194] [Moisture content of strontium titanate particles] The moisture content of each of the strontium titanate particles before being externally added to the toner particles was measured as a sample by the above-mentioned measuring method. The measurement results are shown in Table 1.
[0195] [Mass ratio of strontium titanate particles (Si / Sr)] The strontium titanate particles before being externally added to the toner particles were used as samples to measure the mass ratio (Si / Sr) by the above-mentioned measuring method. The measurement results are shown in Table 1.
[0196] [Average circularity of toner particles] The toner particles before the external additives were added were analyzed using a flow type particle image analyzer (Sysmex Corporation, FPIA-3000) to determine the circularity = (perimeter of a circle having the same area as the projected image of a particle) ÷ (perimeter of the projected image of a particle). The circularity that was 50% cumulatively from the smallest side in the circularity distribution of 3,000 toner particles was determined as the average circularity of the toner particles.
[0197] In addition, when an external additive is added to the toner particles, the above measurement is performed after removing the external additive with a relatively large particle size (for example, an external additive with a primary particle size of 100 nm or more). The operation for removing the external additive is as follows. In a 200 mL glass bottle, add 0.2% by mass of Triton X-100 aqueous solution (Acros Or 40 mL of a 100% ethanol (manufactured by ganics) and 2 g of toner are added and stirred 500 times to disperse the mixture. Next, while maintaining the temperature of the dispersion at 20°C ± 0.5°C, ultrasonic waves are applied using an ultrasonic homogenizer (manufactured by Nippon Seiki Seisakusho, US-300AT). The ultrasonic waves are applied continuously for 300 seconds, with an output of 75 W, an amplitude of 180 μm, and a distance of 10 mm between the ultrasonic transducer and the bottom of the container. Next, the dispersion is centrifuged at 3000 rpm for 2 minutes at a cooling temperature of 0°C using a small high-speed cooling centrifuge (manufactured by Sakuma Seisakusho, M201-IVD), the supernatant is removed, and the remaining slurry is filtered with filter paper (manufactured by Advantec, qualitative filter paper No. 5C, 110 nm). The residue on the filter paper is washed twice with ion-exchanged water and dried to obtain a measurement sample.
[0198] <Evaluation> The obtained developer of each example was placed in the developing device of a modified image forming apparatus "ApeosPort-IV C5575 (manufactured by Fuji Xerox Co., Ltd.)" (modified with the automatic density control sensor for environmental fluctuations removed). Using this modified image forming device, we performed a fog evaluation when outputting 30 A4 sheets of images with an image density of 1% immediately after turning on the image forming device in a high temperature and high humidity environment (28°C / 85% RH environment) and a low temperature and low humidity environment (10°C / 15% RH environment). The evaluation results are shown in Table 2. The evaluation criteria are as follows: G1: No overlaps are permitted on any of the 30 sheets. G2: There is a slight amount of fogging on one sheet, but it is within the practically acceptable range. G3: Slight fogging is observed on multiple sheets, but is within the practically acceptable range. G4: Obvious fogging is observed on multiple sheets, and it is not suitable for practical use. G5: There is complete overlap on all 30 sheets.
[0199] [Table 2] [Explanation of symbols]
[0200] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (an example of a charging means) 3 Exposure device (an example of an electrostatic image forming means) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device (an example of developing means) 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer means) 6Y, 6M, 6C, 6K Photoconductor cleaning device (an example of an image carrier cleaning means) 8Y, 8M, 8C, 8K Toner cartridge 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer means) 28 Fixing device (an example of fixing means) 30 Intermediate transfer belt cleaning device (an example of an intermediate transfer body cleaning means) P Recording paper (an example of a recording medium)
[0201] 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of charging means) 109 Exposure device (an example of electrostatic image forming means) 111 Developing device (an example of developing means) 112 Transfer device (an example of a transfer means) 113 Photoconductor cleaning device (an example of an image carrier cleaning means) 115 Fixing device (an example of fixing means) 116 Mounting Rail 117 Cabinet 118 Exposure Aperture 200 Process Cartridge 300 Recording paper (an example of a recording medium)
Claims
1. A toner particle and a strontium titanate particle externally added to the toner particle, the strontium titanate particles present on the surface of the toner particles have an average primary particle size of 30 nm or more and 100 nm or less, an average circularity of the primary particles of 0.82 or more and 0.94 or less, and a circularity of 84% of the cumulative primary particles exceeds 0.92; the strontium titanate particles are doped with a metal element other than titanium and strontium and have surfaces that have been subjected to a hydrophobic treatment with a silicon-containing organic compound; The toner for developing electrostatic images has a water content of the strontium titanate particles of 2% or more and 5% or less.
2. 2. The toner for developing electrostatic images according to claim 1, wherein the mass ratio (Si / Sr) of silicon (Si) to strontium (Sr) calculated from qualitative and quantitative analysis of fluorescent X-ray analysis of the strontium titanate particles is 0.025 or more and less than 0.
09.
3. 3. The toner for developing electrostatic images according to claim 1, wherein the strontium titanate particles present on the surfaces of the toner particles have a standard deviation of circularity of primary particles of 0.04 or more and 2.0 or less.
4. 4. The toner for developing electrostatic images according to claim 3, wherein the strontium titanate particles present on the surface of the toner particles have a standard deviation of circularity of primary particles of 0.04 or more and 1.0 or less.
5. The toner for developing electrostatic images according to any one of claims 1 to 4, wherein the strontium titanate particles have a surface containing 5% by mass or more and 30% by mass or less of a silicon-containing organic compound relative to the mass of the strontium titanate particles.
6. 6. The toner for developing electrostatic images according to claim 5, wherein the strontium titanate particles have a surface containing 10% by mass or more and 25% by mass or less of a silicon-containing organic compound based on the mass of the strontium titanate particles.
7. 7. The toner for developing electrostatic images according to claim 1, wherein the silicon-containing organic compound is at least one selected from the group consisting of alkoxysilane compounds and silicone oils.
8. 8. The toner for developing electrostatic images according to claim 1, wherein a surface coverage rate of the strontium titanate particles relative to the toner particles is 3% or more and 50% or less.
9. 9. The toner for developing electrostatic images according to claim 8, wherein a surface coverage rate of the strontium titanate particles with respect to the toner particles is 5% or more and 30% or less.
10. 10. The toner for developing electrostatic images according to claim 1, wherein the strontium titanate particles are lanthanum-doped strontium titanate particles.
11. The toner for developing electrostatic images according to any one of claims 1 to 10, wherein the strontium titanate particles present on the surface of the toner particles have an average primary particle size of 30 nm or more and 80 nm or less.
12. 12. The toner for developing electrostatic images according to claim 11, wherein the strontium titanate particles present on the surface of the toner particles have an average primary particle size of 30 nm or more and 60 nm or less.
13. The toner for developing electrostatic images according to any one of claims 1 to 12, wherein the toner particles have an average circularity of 0.91 or more and 0.98 or less.
14. The toner for developing an electrostatic image according to claim 13, wherein the average circularity of the toner particles is 0.93 or more and 0.97 or less.
15. The toner for developing an electrostatic image according to any one of claims 1 to 14, wherein the toner particles are white toner particles.
16. 16. An electrostatic image developer comprising the toner for developing electrostatic images according to claim 1.
17. The toner for developing an electrostatic image according to any one of claims 1 to 15 is contained therein, A toner cartridge that is detachably attached to an image forming apparatus.
18. a developing unit that contains the electrostatic image developer according to claim 16 and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus.
19. An image carrier; a charging means for charging the surface of the image carrier; an electrostatic image forming means for forming an electrostatic image on the charged surface of the image carrier; a developing unit that contains the electrostatic image developer according to claim 16 and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer means for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing means for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising:
20. a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; An electrostatic image formed on the surface of the image carrier by the electrostatic image developer according to claim 16. a developing step of developing the toner image; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1,
Citation Information
Patent Citations
Melting method of refining slag* having alkali metal compounds for its chief ingredients
JP1977048511A
Two-component developer
JP2010044113A
Toner for electrostatic image development, electrostatic image developer, and image forming method
JP2011137980A
Image forming apparatus
JP2011203758A
Strontium titanate-based fine particle for toner and manufacturing method therefor
JP2018020919A